French and Indians in the Heart of North America, 1630-1815 - Teasdale, Guillaume; Englebert, Robert (Book collections on Project MUSE., 2013)
The study of French-Indian relations in the center of North America has emerged as an important field for examining the complex relationships that defined a vast geographical area, including the Great Lakes region, the Illinois Country, the Missouri River Valley, and Upper and Lower Louisiana. For years, no one better represented this emerging area of study than Jacqueline Peterson and Richard White, scholars who identified a world defined by miscegenation between French colonists and the native population, or metissage, and the unique process of cultural accommodation that led to a middle ground between French and Algonquians. Building on the research of Peterson, White, and Jay Gitlin, this collection of essays brings together new and established scholars from the United States, Canada, and France, to move beyond the paradigms of the middle ground and metissage. At the same time, it seeks to demonstrate the rich variety of encounters that defined French and Indians in the heart of North America from 1630 to 1815. Capturing the complexity and nuance of these relations, the authors examine a number of thematic areas that provide a broader assessment of the historical bridge-building process, including ritual interactions, transatlantic connections, diplomatic relations, and post-New France French-Indian relations.